Revolt and Rule: Learning about Governance from Rebel Groups. Issue 4 (22nd September 2022) - Loyle, Cyanne E; Braithwaite, Jessica Maves; Cunningham, Kathleen Gallagher; Huang, Reyko; Huddleston, R Joseph; Jung, Danielle F; Rubin, Michael A
Abstract: Recent work in international relations has problematized state-centric assumptions of governance to explore variations in authority by a range of nonstate actors (e.g., nongovernmental organizations, criminal syndicates, gangs). This forum centers on the phenomenon of rebel group governance during civil wars and leverages the concept to advance our understanding of current theories and conceptualizations of governance. The nature of rebel organizations provides a unique opportunity for researchers to expand the state-centric focus on governance because rebel actors differ from states in their comparative position within the global state system, the contexts in which they operate, and their lack of legitimizing principles that permit consistent membership as a class of political actors. These differences allow for meaningful extensions of how we theorize and conceptualize governance beyond the state. Furthermore, variation across these differences allows our findings in the study rebel governance to speak directly to the broader literature in international relations on governance by state actors. In our introduction to this forum, we detail the ways in which rebel groups have chosen to address the central components of governance through a variety of governance strategies. We then devote three essays in the forum to the concepts of legitimacy, capacity, and territorial control. In each of the three essays, authors discuss the ways in which rebel governance problematizes and advances these concepts for the broader study of governance. In the conclusion, this forum synthesizes extant and emerging work in the field of rebel governance in order to raise new questions of the governance and state building literatures. In this way, we show how investigating governance by rebel groups in particular advances our understanding of governance more broadly.